Penanganan Penyakit Jantung Pada Ibu Hamil - Riky Riky; Destinady Destinady; Fina Ratih Wira Putri Fitri Yani; Raodatul Jannah (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2021)
Abstract – Pregnant women with heart disease cannot be denied, even though heart disease is a disease that is considered serious and can pose a risk of death. Treatment of pregnant women with heart disease must be carried out carefully to minimize the occurrence of dangerous risks for both the mother and the fetus. Therefore researchers want to find out more about the treatment of heart disease in pregnant women. The purpose of this study is to find out the appropriate handling procedures for pregnant women with heart disease. The research method used is qualitative with library research so that the data collected is in the form of a variety of information that is spread either through journals, research or books according to the research objective. The data found were then analyzed to find out the results of the research. The results of the study show that if a patient is known to have heart disease before pregnancy, he or she usually has to consult first with the cardiologist who handles it. However, if you don't have a history of heart disease before, you will continue to be monitored by a multidisciplinary doctor to reduce the risk of harm to both the pregnant woman and the fetus, bearing in mind that during pregnancy the heart works harder than when you are not pregnant.